An improved particle swarm optimization based on the reinforcement of the population initialization phase by scrambled Halton sequence. Issue 1 (1st January 2020) - Digehsara, Pouriya Amini; Chegini, Saeed Nezamivand; Bagheri, Ahmad; Roknsaraei, Masoumeh Pourabd
Abstract: The use of meta-heuristic methods for solving nonlinear engineering and optimization problems is one of the paramount topics that attracted the attention of the researchers. Particle swarm optimization (PSO) is an optimization algorithm which has inspired by birds flocking. However, like other methods, PSO has some disadvantages such as problems in finding the best global minimum or trapping in the local minima in some special problems. In some works, the initial particles are randomly set using uniform or Gaussian distributions. These particles sometimes fail to cover the search space completely. The main goal of this paper is to improve the mechanism of the initial population production stage in the first step to cover the feasible space properly. So, with the help of the scrambled Halton sequence and producing quasi-random numbers, the initial population has been generated in a mathematical way without making a lot of change in the original PSO algorithm and its structure. These particles cover the search space more efficiently. This new hybrid algorithm is named the Halton-PSO in this research. The results show that Halton-PSO improves the ability and efficiency of PSO. The performance and ability of the proposed Halton-PSO algorithm have been examined by 11 benchmark functions and 7 different nonlinear engineering problems. Both of the optimization results of test functions and the real problems demonstrate that the Halton-PSO method is more successful than the original PSO and the PSO family algorithms and the other methods for distinguishing the global best minimum.